Plant metabolism : - Sriram, Ganesh,Ed (Methods in Molecular Biology,, 2014)
In Plant Metabolism: Methods and Protocols, expert researchers in the field present the latest methods on quantitative analysis of plant metabolism. The methods focus on measurements, analyses and simulations of molecules, fluxes, and ultimately entire metabolic pathways and networks. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials, reagents, or software, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Plant Metabolism: Methods and Protocols seeks to benefit scientists ranging from plant biology, metabolic engineering, and biotechnology.--